China returns to Africa a rising power and a continent embrace - Alden, Chris (London Hurst, 2008)
China Returns to Africa presents the first in-depth, far-ranging survey of china Africa relations. Contributions by an international team of experts in African and Chinese affairs provide an analytically rich, empirically grounded assessment of the changing nature of trade,politics and society in the wake of China's growing prominence in Africa.Analysis of key economic and political trends is augmented by chinese, African, European and American perspectives and anchored in detailed country case-studies.This book concludes by considering what the implications of China's engagement holds for the future of African continent.
bibliographical references
Keywords: Economic Conditions